АНАЛІЗ ПОНИЖУВАЛЬНО-ПІДВИЩУВАЛЬНИХ НЕІНВЕРТУЮЧИХ ПЕРЕТВОРЮВАЧІВ ПОСТІЙНОЇ НАПРУГИ З ВИКОРИСТАННЯМ МЕТОДА УСЕРЕДНЕННЯ - Руденко, Ю.В. (Інститут електродинаміки НАН України, Київ, 2026)
The processes in non-inverting DC-DC buck-boost converters were investigated: using the elementary topology and the positive output Luo topology (PO Luo converter). Using the averaging method based on Lagrange theorems, analytical models and expressions have been developed for calculating and analyzing the average, pulsating components of processes in converters, including output voltage pulsations in continuous and discontinuous conduction modes across the entire switching range. The developed analytical models allow us to refine and simplify the calculation of processes in converters relative to existing calculation methods. Analytical conditions have been developed that allow predicting the degree of reduction in output voltage ripple in the PO Luo converter compared to the base circuit. Analytical and graphical dependence on the limiting values of the parameters of PO Luo converter in full commutation range between CCM and DCM modes was obtained, which makes it possible to reasonably choose its parameters at the design stage. The results of simulation modeling of processes in the PO Luo converter confirmed the correctness of the developed analytical relationships. The discrepancy between the results of process calculations according to the developed analytical models and simulation modeling does not exceed 1%. References 12, figures 6, tables 3.